Result of management of closed distal radial fracture by Ayjaz Azim foundation mini external fixator - Dutta, Shawon; Kundu, Sujit; Musa, Mohammad; Rahman, Mohammad Sanaur (International Journal of Research in Orthopaedics, 2025)
Background: Distal radius fractures are one of the most common orthopedic conditions and intra-articular types (AO/ASIF type C) are difficult to treat. While various treatment options exist, external fixation remains valuable, particularly in the developing world. The present study evaluated the efficacy of the Ayjaz Azim foundation (AAF) mini external fixator for the treatment of closed, complete articular distal radius fractures. Methods: This study evaluated outcomes in 32 patients with closed intra-articular distal radial fractures by purposive sampling. Patients between 18 and 60 years, within two weeks of injury, received standardized surgery. Structured questionnaires were used to collect data, and outcomes at 12 weeks after surgery were assessed using Sarmiento's radiological criteria and the Green and O'Brien functional scoring system. Statistical analysis was performed with SPSS v26, and significance was at p<0.05. Results: The study population (41.63±12.39 years) had a predominance of males (78.1%), and the most common injury mechanism was motor vehicle accidents (68.75%). Surgery was performed in 90.6% of patients within 24 hours of trauma. Radiologically, 62.5% had excellent results, 31.3% good, and 6.3% fair. The mean loss of volar tilt was 5.03°±3.84°, radial shortening 2.47 mm±2.27 mm, and radial inclination 4.03°±3.27°. Functionally, 62.5% had excellent results, 21.9% good, 12.5% fair, and 3.1% poor. Pin tract infection occurred in 16% of the cases and post-removal stiffness in 62.5% of patients. Radiological and functional results had a good correlation (r=0.876, p<0.001). Conclusions: AAF mini external fixator is a useful tool for the treatment of AO/ASIF type C distal radius fractures, with 94% patients showing satisfactory results. The technique is reliable for anatomical reconstruction and functional rehabilitation with acceptable complication rates and is a well-suited treatment method worthy of consideration, particularly in regions with limited resources.